Effectiveness of lactate threshold exercises in the concentration of lactic acid in blood and in the endurance performing layups in under 18-years of age basketball players - Nidal Obed Hamza; Hussein Mnaty Sachit; ‏Ali Kareem Finteel; Abbas Abdulhamza Kadhem (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.